Phenomenological Subjectivity аs an Intersection Between Philosophy and Literature - Tasevska Hadji Boshkova, Iskra (Sapienza University of Rome and Mediterranean Center of Social and Educational Research, 2012)
Thorough depiction of the problem of phenomenological subjectivity is a profound, and contemporary challenge. Investigations of young and late Husserl, as well as his successors (that upgraded the phenomenological project) – Martin Heidegger, Roman Ingarden, Jacques Derrida, Roland Barthes, Michel Foucault, etc. should provide us with a large interdisciplinary context, especially between philosophy and literary criticism. The question of subjectivity is something which contemporary epistemology cannot deny – it is dominant aspect in the domains of literary theory (author, narrator, reader), as well as in philosophical inquiries (practical, metaphysical, transcendental subject, etc.). This paper aims to reunite this concept within a wider context – the question of subjectivity is more than 19th century, modern, or postmodern product. It concerns the provisional status of subject as existential Sein, but also the possibility to consider postmodern subjectivity as its confirmation. On the one hand, in Derrida’s terms, solicitation is the movement of self, destruction of totality, but on the other it is also “being “ as presence in the living present, that ultimately is not available for diminution, especially because its uniformity cannot be theoretically grasped.
Keywords: phenomenology, subjectivity, reader, author, interdisciplinary bond, intersubjectivity